ANALYSIS OF IPA PRACTICUM AT THE MTs LEVEL IN REJOTANGAN TULUNGAGUNG SUB-DISTRICT - Agustin, Haslinda Yasti (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Core Competencies and Basic Competencies at SMP/MTs are essential curriculum components that determine learning outcomes, especially in science subjects whose contents refer to several practical activities. Practicum activities are a form of learning carried out in a specific place where students play an active role in solving problems through specific tools, materials and methods. This activity can be carried out at school in a science laboratory because it is supported by various adequate laboratory equipment and materials. There are various problems related to the implementation of science practicum, especially in several MTs in the Rejotangan Tulungagung District area. Some of the problems include the absence of laboratory space, practicum tools and materials, practicum manuals, practicum time that is too short, laboratory personnel and laboratory documents, and the competence of educators who are not suitable for science subjects. The solution to the problem is holding simple science practicum training for teachers, laboratory management training, and maximizing cooperative relations with universities.